2001
DOI: 10.1523/jneurosci.21-24-09519.2001
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-9 Activation Results in Downstream Caspase-8 Activation and Bid Cleavage in 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine-Induced Parkinson's Disease

Abstract: Parkinson's disease (PD) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) toxicity are both associated with dopaminergic neuron death in the substantia nigra (SN). Apoptosis has been implicated in this cell loss; however, whether or not it is a major component of disease pathology remains controversial. Caspases are a major class of proteases involved in the apoptotic process. To evaluate the role of caspases in PD, we analyzed caspase activation in MPTP-treated mice, in cultured dopaminergic cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
191
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(210 citation statements)
references
References 62 publications
16
191
1
2
Order By: Relevance
“…t-Bid then translocates to the outer mitochondrial membrane and promotes oligomerization of Bax or Bak to facilitate release of cytochrome c and subsequent caspase-9 activation (Li et al, 1998;Luo et al, 1998). In addition, a caspase-9-mediated caspase-8 activation has been reported in certain cell systems (Cha et al, 2001;Viswanath et al, 2001). Although our results show clearly the involvement of Figure 5 PI3-K inhibition partially reverses the CEA-mediated inhibition of caspase-9 and -3 activity.…”
Section: Discussionmentioning
confidence: 47%
“…t-Bid then translocates to the outer mitochondrial membrane and promotes oligomerization of Bax or Bak to facilitate release of cytochrome c and subsequent caspase-9 activation (Li et al, 1998;Luo et al, 1998). In addition, a caspase-9-mediated caspase-8 activation has been reported in certain cell systems (Cha et al, 2001;Viswanath et al, 2001). Although our results show clearly the involvement of Figure 5 PI3-K inhibition partially reverses the CEA-mediated inhibition of caspase-9 and -3 activity.…”
Section: Discussionmentioning
confidence: 47%
“…This demonstrates, first, an increase in the activation of the pro-interleukin-1␤ converting enzyme (caspase-1) and, second, an increased potential for stimulating the caspase-8 activating TNF-␣ receptors on the dopaminergic neurons. This is corroborated by the increased activity of caspase-1 in substantia nigra from patients with Parkinson's disease as compared with substantia nigra from control patients (37) and by the demonstration of increased levels of activated caspase-8 in dopaminergic neurons of the substantia nigra in patients with Parkinson's disease compared with control patients (38,39). Caspase-8 is also activated in the MPTP mouse model of Parkinson's disease (38,39).…”
Section: Endogenous Caspase-8 But Not Endogenous Caspase-3 Cleaves mentioning
confidence: 74%
“…Therefore, we concluded that the noncell-autonomous effect in which caspase-11 is expressed on microglia is the major effector of dopaminergic neuronal death in the acute MPTP model. Notwithstanding these findings, several studies have shown that acute MPTP treatment results in activation of caspase-3 in dopaminergic neurons (Viswanath et al, 2001). Therefore, we assume that a few caspase-11-positive dopaminergic neurons may die through the apoptotic cascade, via the cell-autonomous effect.…”
Section: Discussionmentioning
confidence: 87%